Heavy water hydration of mannose: the anomeric effect in solvation, laid bare - Mayorkas, N; Rudic, S; Davis, B; Simons, J (2011)
The presence and consequences of the anomeric effect have been explored and directly exposed, through an investigation of the vibrational spectroscopy of the doubly and triply hydrated a and b anomers of phenyl D-mannopyranoside, (PhMan) isolated under molecular beam conditions in the gas phase. The experiments have been aided by the simple trick of substituting D2O for H2O, which has the advantage of isotopically isolating the carbohydrate (OH) bands from the water (OD) bands. Recording the double resonance, IR-UV ion dip spectra of the hydrated complexes, a- and b-PhMan·(D2O)2,3 in a series of 'proof of principle' experiments, revealed that these heavy water molecules engage the key endocyclic oxygen atom, O5, allowing the anomeric effect to be probed through a combination of vibrational spectroscopy and quantum chemical calculations. Importantly, in the dihydrates, both anomers adopt the same conformation and the two water molecules occupy the same template. One of them acts as a remarkably sensitive reporter, able to sense and expose subtle stereoelectronic changes through the resulting changes in its hydrogen-bonded interaction with the substrate. © The Royal Society of Chemistry 2011.